Incidence of effort-reward imbalance among nurses: a systematic review and meta-analysis - Zhang, Yujie; Lei, Shanyan; Yang, Fang (Frontiers in Psychology, 2024)
Introduction To systematically evaluate the incidence of effort-reward imbalance among nurses. Method PubMed, Web of Science, Embase, CNKI, WanFang Data, and VIP databases were searched to collect studies on the incidence of effort-reward imbalance among nurses. The search timeframe was from database construction to December 2023. Two researchers independently screened the literature, extracted the data, and evaluated the risk of bias in the included studies. The meta-analysis was performed using Stata 17.1 software. Results A total of 60 studies, including 79,644 participants, were included. The prevalence of effort-reward imbalance among nurses was 52.3% (95% CI: 44.9–59.7%). In terms of time, the incidence of effort-reward imbalance among nurses before 2010 (26.6, 95%CI: 6.8–46.4%) and in 2010–2015 (42.4, 95%CI: 32.1–52.8%), 2016–2020 (60.2, 95%CI: 49.6–70.7%), and 2021–2023 (65.0, 95%CI: 51.5–78.4%) continued to increase. Geographically, Asia (57.4, 95%CI: 51.8–63.1%) nurses had a relatively higher prevalence of effort-reward imbalance. In terms of department, the incidence of effort-reward imbalance among nurses was relatively higher in operating rooms (71.8, 95%CI: 64.5–79.0%), ICU (64.6, 95%CI: 27.7–100.0%), emergency (68.7, 95%CI: 62.9–74.5%), and pediatrics (65.8, 95%CI: 32.2–99.3%). Discussion The prevalence of nurse effort-reward imbalance is high, and there are differences in its prevalence across time, geography, department. Hospital administrators should actively take measures to effectively prevent and reduce the effort-reward imbalance for nurses, especially for nurses in Asia, operating rooms, emergency pediatrics and ICU departments. Systematic review registration PROSPERO (CRD42023452428).